INFOGRAPHIC UTILIZATION OF FLOWS TO IMPROVE UNDERSTANDING OF PASSPORT APPLICATIONS THROUGH SOCIAL MEDIA IN THE CLASS II IMMIGRATION OFFICE OF TPI CILACAP - Hafidz Dzulfauzi Rahman (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2019)
Infographic comes from the English word Infographic which stands for information and graphic, which means a form of information visualization that delivers complex data to the reader so that it can be understood more easily and quickly. The purpose of this research is to find out how to use the Infographic at the Class II Immigration Office of TPI Cilacap and to find out how the public understands the passport application with the Infographic at the Class II Immigration Office of TPI Cilacap. This research provides information and understanding about passport application to the public through Infographics at the Class II Immigration Office of TPI Cilacap and provides input on consideration and evaluation in the utilization of inforafis at the Class II Immigration Office of TPI Cilcap. In this research using qualitative research method. The results of the study are known to the average resource person between 18 - 35 years old, this can be said as a young reader or digital natives and it is known that the Class II Immigration Office of TPI Cilacap innovates the form of content in its instragram account into Infographics. The Class II Immigration Office of TPI Cilacap uses the Infographic as a medium to convey various kinds of information about immigration through social media. In the case of making Infographics Of Class II Immigration Office TPI Cilacap needs to follow the development of existing trends.